Correlation between territorial innovative clusters and sustainable development of a region - A. A. Korableva; V. V. Karpov; E. A. Kapoguzov (Russian Journal of Economics and Law)
Objective: to substantiate the list of indicators of a region sustainable development, taking into account the impact of territorial innovation clusters on regional socio-economic processes.Methods: general scientific methods of cognition were used in the process of research; the formation of the territorial innovation cluster model as a mechanism of the region sustainable development is based on the grouping of factors of the external and internal environment of the cluster; using the methods of analogy and comparison, a list of indicators of the region sustainable development was formed, taking into account the generalized factors of territorial clusters’ development. Results: improving the competitiveness of Russian regions is one of the most important areas of state economic policy undeer modern conditions. Based on the analysis of scientific literature and state strategic documents, the article reveals the main approaches to the definition of sustainable development of territories. The target parameters of the region sustainable development, stipulated by the federal and regional normative legal acts, are revealed. The indicators of sustainable development of territories are studied and systematized, as well as tools and mechanisms to ensure them. It is found that within the scientific and practical environment a significant place should be given to research, methodologically or empirically determining the quality of the relationship between the sustainable development of the region and the activities of territorial innovation clusters. On the basis of the author’s model of activity of the territorial innovation cluster, the subjects and directions of their interaction within the cluster are defined. The factors of the external and internal environment of the territorial innovation cluster, determining the successful development of the cluster, are determined. A list of indicators of regional sustainable development is formed, corresponding to the factors of the territorial innovation cluster development.Scientific novelty: based on the proposed approach, the role of territorial innovation clusters is shown as an element of the sustainable regional development mechanism through the vectors of influence of the cluster external and internal environment on the indicators of the region sustainable development.Practical significance: the obtained results can be used as recommendations for regional authorities’ forming the target indicators and expected results of cluster policy to ensure sustainable development.